2018
DOI: 10.1007/s00442-018-4198-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the interplay between canopy energy balance and photosynthesis with cellulose δ18O: large-scale patterns and independent ground-truthing

Abstract: There are few whole-canopy or ecosystem scale assessments of the interplay between canopy temperature and photosynthesis across both spatial and temporal scales. The stable oxygen isotope ratio (δO) of plant cellulose can be used to resolve a photosynthesis-weighted estimate of canopy temperature, but the method requires independent confirmation. We compare isotope-resolved canopy temperatures derived from multi-year homogenization of tree cellulose δO to canopy-air temperatures weighted by gross primary produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…In instances where an annual or multi‐annual average of δ18O is used, it is often assumed that the relative variability of VPD is larger than δ18O of source water. Therefore, changes in the isotopic ratio of signal are more strongly affected by canopy conditions than plant water use (Helliker et al, ). However, when annual growth rings are subsampled to produce seasonal cycles in δ18O, changes in the source water over the growing season may be large enough to supersede the effects of changing VPD.…”
Section: Introductionmentioning
confidence: 99%
“…In instances where an annual or multi‐annual average of δ18O is used, it is often assumed that the relative variability of VPD is larger than δ18O of source water. Therefore, changes in the isotopic ratio of signal are more strongly affected by canopy conditions than plant water use (Helliker et al, ). However, when annual growth rings are subsampled to produce seasonal cycles in δ18O, changes in the source water over the growing season may be large enough to supersede the effects of changing VPD.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope modeling is not devoid of uncertainties concerning the precision of the approach at short temporal scale, for example, variability of isotopic fractionation factors and within‐plant carbon cycling (Helliker et al., 2018; Sternberg, 2009). Yet, the agreement between isotope‐resolved canopy temperature and eddy covariance measurements confirmed that our current knowledge of the theory provides estimates of T L with satisfying accuracy for broad scales studies encompassing acute climatic variation and multi‐year integrations (Helliker et al., 2018). Since biochemical and physiological parameters used in the tree‐ring cellulose model were originally derived from non‐woody species (e.g., Barbour, Schurr, Henry, Wong, & Farquahr, 2000; Helliker & Ehleringer, 2002; Sternberg, DeNiro, & Savidge, 1986), such modeling approach can be expanded to non‐tree species as well (e.g., Michaletz et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fine‐scale sampling of secondary growth, isotopic composition and wood anatomical features has enabled the study of intra‐seasonal tree growth dynamics in response to environmental and ecophysiological processes (Helle & Schleser, ; Gessler et al , ; Treydte et al , ; Sargeant & Singer, ; Cuny et al , ; Helliker et al , ; Monson et al , ), and this fine‐scale sampling approach has led to a re‐examination of our fundamental understanding of how environmental factors are recorded in δ 18 O of cellulose (δ 18 O cell ) (Roden et al , ; Cheesman & Cernusak, ). The intra‐annual record of δ 18 O cell can be decoupled from the climate variables under which the cambial cells are produced, and this decoupling can be related to temporal lags in xylogenesis and post‐carboxylation processes (Lévesque et al , ; Belmecheri et al , ; Nabeshima et al , ; Szejner et al , ).…”
Section: Introductionmentioning
confidence: 99%